Concurrent TP53 and CDKN2A Gene Aberrations in Newly Diagnosed Mantle Cell Lymphoma Correlate with Chemoresistance and Call for Innovative Upfront Therapy - Malarikova, Diana; Berkova, Adela; Obr, Ales; Blahovcova, Petra; Svaton, Michael; Forsterova, Kristina; Kriegova, Eva; Prihodova, Eva; Pavlistova, Lenka; Petrackova, Anna; Zemanova, Zuzana; Trneny, Marek; et al. (Cancers, 2020)
Mantle cell lymphoma (MCL) is a subtype of B-cell lymphoma with a large number of recurrent cytogenetic/molecular aberrations. Approximately 5-10% of patients do not respond to frontline immunochemotherapy. Despite many useful prognostic indexes, a reliable marker of chemoresistance is not available. We evaluated the prognostic impact of seven recurrent gene aberrations including tumor suppressor protein P53 (TP53) and cyclin dependent kinase inhibitor 2A (CDKN2A) in the cohort of 126 newly diagnosed consecutive MCL patients with bone marrow involvement ≥5% using fluorescent in-situ hybridization (FISH) and next-generation sequencing (NGS). In contrast to TP53, no pathologic mutations of CDKN2A were detected by NGS. CDKN2A deletions were found exclusively in the context of other gene aberrations suggesting it represents a later event (after translocation t(11;14) and aberrations of TP53, or ataxia telangiectasia mutated (ATM)). Concurrent deletion of CDKN2A and aberration of TP53 (deletion and/or mutation) represented the most significant predictor of short EFS (median 3 months) and OS (median 10 months). Concurrent aberration of TP53 and CDKN2A is a new, simple, and relevant index of chemoresistance in MCL. Patients with concurrent aberration of TP53 and CDKN2A should be offered innovative anti-lymphoma therapy and upfront consolidation with allogeneic stem cell transplantation.
Keywords: TP53; CDKN2A; prognostic markers; chemoresistance; mantle cell lymphoma